On the structural evolution of Central and Eastern Afghanistan - Bordet, P. (Journal of Himalayan Earth Sciences, 1980)
The Central and Eastern Afghanistan are constituted by blocks of continental basement separated by depressions associated with strike-slip faults showing present-day activity. There are W-E to SW-NE faults converging in the Kabul region. One may distinguish 4 main blocks: Hindu Kush, Band-e-Bayan, Central Ranges and Ealouch Province. They are separated by: the Bameyan trough associated with the Herat fault; the Panjaw trough is connected with the Helmand fault and the Kandhar trough connected with Chaman-Argandch fault.